The Effect of Process Picture-Based Momentum and Impulse LKPD on Creative Thinking Ability and Physics Learning Outcomes of High School Students - Herlia, Naziroh Faiqohtul; Sutarto, Sutarto; Meilina, Ike Lusi; Indrawati, Indrawati (Navigation Physics : Journal of Physics Education, 2025)
Physics learning in the 21st century era needs to be directed to develop the abilities needed in the future, one of which is the ability to think creatively. The use of LKPD can help students understand certain concepts and create student-oriented physics learning. This study aims to examine the effect of process image-based momentum and impulse LKPD on students' creative thinking ability and physics learning outcomes. The type of research used was quasi experiment with nonequivalent control group design. This research was conducted at MAN 2 Jember with the population used was the entire class XI. The research sample was taken by cluster sampling to determine the experimental class and control class. In this study using instruments in the form of creative thinking ability test and physics learning outcomes test of students. Data analysis used in this study is using independent sample t-test. The results obtained a significance value of 0.000 in creative thinking ability and 0.002 in student learning outcomes which shows the Sig. (2-tailed) value <0.05 then H0 is rejected and Ha is accepted, meaning there is a significant difference between the control class and the experimental class. The conclusion of this study is that the momentum and impulse LKPD based on process images has a significant effect on students' creative thinking ability and physics learning outcomes.